Long-term monitoring of PCDD/Fs in soils in the vicinity of a hazardous waste incinerator in China: Temporal variations and environmental impacts - Lin, Xiaoqing; Li, Min; Chen, Zhiliang; Chen, Tong; Li, Xiaodong; Wang, Chao; Lu, Shengyong; Yan, Jianhua (The Science of the total environment, 2020)
Campaigns from 2008 to 2016 are carried out to study temporal variations and environmental impacts of polychlorinated dibenzo-p-dioxin and dibenzofuran (PCDD/Fs) in soils in the vicinity of a new hazardous waste incinerator (HWI) in China. Results indicate that after 8-year operation of HWI, the geometrical means of both the total concentrations and the TEQ values of PCDD/Fs in soils decrease from 1280 ng·kg−1 and 3.08 ng WHO-TEQ·kg−1 to 568 ng·kg−1 and 2.70 ng WHO-TEQ·kg−1, respectively, showing generally limited impact on soils within 7.5 km. Temporal changes of PCDD/Fs congener profiles trend to profiles in combustion sources. Considering the whole studied area, results of principal component analysis between soils and emission sources show that instead of HWI, other sources including open burning, traffic, and cement plant are more responsible for PCDD/Fs accumulation. The modeling results of AERMOD indicate the dominant roles of wind velocities and directions on the deposition of PCDD/Fs emitted from HWI. The largest PCDD/Fs increase value in soils predicted by integrating AERMOD and a reservoir model is very limited after 25 years (2.03 × 10−5 ng WHO-TEQ·kg−1), indicating relatively minor impacts of HWI on surrounding soils, but the noticeable impact on area downwind from the stack in short distance (e.g., within 0.5 km) should be recognized. [Display omitted] •8-Year operation of HWI has a very limited impact on neighboring soils generally.•Sites downwind from the stack with short distance are evidently influenced by the HWI.•Deposition of PCDD/Fs from HWI is mainly subject to wind velocities and directions.•AERMOD modeling results reveal minor impacts of HWI on surrounding soils.